Українська історіографічна проза XVIII – першої половини XIX ст. в оцінці Михайла Максимовича - Мишанич, Я.В. (Слово і Час, 2019)
У статті проаналізовано праці історика Михайла Максимовича, у яких ідеться про три твори, написані у XVIII – XIX ст. – літопис Григорія Граб'янки, “Історію Русів” і “Чорну раду” П. Куліша. Наукова історіографія на той час іще не виокремилася як наука, тому відповідні словесні пам'ятки могли мати риси як художнього, так і наукового дискурсу. Критичне ставлення вченого до літопису Григорія Граб'янки змінюється на поблажливе у випадку з “Історією Русів” та на виважено-критичне до “Чорної ради” П. Куліша. М. Максимович, спираючись на праці попередників і сучасників, досить чітко окреслив певні рамки, у яких належало перебувати науковій історіографічній розвідці, водночас віддаючи належне художньому творові, сюжет якого побудований на історичних подіях. The essay reviews the studies of Mykhailo Maksymovych that deal with the three works of the 18th–19th-century Ukrainian historiography. According to M. Maksymovych, one may classify the syncretic historiographic works within three main types. These are Cossack chronicles of the late 17th – early 18th centuries, journalistic pamphlets of the late 18th century, and historical novels of the mid-19th century. The scholar used different approaches analyzing the works from the mentioned groups (chronicle by Hryhorii Hrabianka, “History of Ruthenians”, and “The Commoners’ Council” by Panteleimon Kulish). The scholarly historiography of the time was not still shaped enough and the works from the field could have features of fiction and research studies simultaneously. The authors, who didn’t understand history as a separate research field, were free of modern limits and could easily use both fictional and research techniques within the same work. The strict critical attitude of the scholar towards the chronicle by Hryhorii Hrabianka changed into tolerant in the case of “History of Ruthenians” and moderate critical in the analysis of “The Commoners’ Council”. M. Maksymovych tried to be objective in covering historical processes and worked hard to develop a scholarly approach in the evaluation of Ukrainian historiographical prose. Maksymovych took into account the specificity of every single work and, based on the ideas of his predecessors and contemporaries, rather accurately defined the proper frames of the scholarly historiography. At the same time, the scholar didn’t deny the value of fictional works based on historical events.